Harry Potter and the Order of the Phoenix - Rowling, J. K.; GrandPré, Mary (London : Bloomsbury, 2003)
When the government of the magic world and authorities at Hogwarts School of Witchcraft and Wizardry refuse to believe in the growing threat of a freshly revived Lord Voldemort, fifteen-year-old Harry Potter finds support from his loyal friends in facing the evil wizard and other new terrors.
"Year 5"--Spine.
Sequel to: Harry Potter and the goblet of fire.
Keywords: Wizards -- Fiction; Magic -- Fiction; Schools -- Fiction; Coming of age -- Fiction; England -- Fiction